2002
DOI: 10.1038/sj.bjp.0704847
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐sensitive purinoceptors induce steroidogenesis via adenylyl cyclase activation in bovine adrenocortical fasciculata cells

Abstract: 1 The role of P2Y receptors in the production of cAMP and the activation of protein kinase A (PKA) was studied with respect to the regulation of the steroidogenesis in primary cultures of bovine adrenocortical fasciculata cells (BAFCs). 2 ADP and ATP stimulated cAMP production with EC 50 values of 23.7+6.8 mM and 40.1+5.5 mM, respectively. In contrast, the EC 50 of BzATP for cAMP production was 153.0+37.4 mM. Adenosine and AMP (0.1 ± 1000 mM) were much less e ective than ADP and ATP. 2MeSADP and UTP did not ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…We have already reported that, while ATP and UTP may bind to P2Y 2 receptor, ADP binds to an unidentified P2Y receptor linked to adenylyl cyclase in BAFC (Nishi et al, 2002). Our findings in the present study indicate that ATPgS binds to both purinoceptors.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…We have already reported that, while ATP and UTP may bind to P2Y 2 receptor, ADP binds to an unidentified P2Y receptor linked to adenylyl cyclase in BAFC (Nishi et al, 2002). Our findings in the present study indicate that ATPgS binds to both purinoceptors.…”
Section: Discussionsupporting
confidence: 69%
“…They induce steroidogenesis via the UTP binding sites (e.g. P2Y 2 receptors) (Nishi, 1999) and ADP binding sites (unknown P2Y receptors) (Nishi et al, 2002) in BAFCs. However, the nucleotide potency order on cAMP accumulation and the mRNA level make it unlikely that BAFC has P2Y 1 receptors (Nishi, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that extracellular ATP acts as a modulator of function in different endocrine cell types, including Sertoli cells [16], spermatogonia [32], granulosaluteal cells [47], and adrenocortical fasciculate cells [39]. In Leydig cells of rats and mice, ATP leads to an increase in intracellular calcium concentration ([Ca 2+ ] i ) and subsequent testosterone secretion [17,40].…”
Section: Introductionmentioning
confidence: 99%